Mucin secretion is modulated by luminal factors in the isolated vascularly perfused rat colon. Issue 2 (1st February 2000) - Barcelo, A; Claustre, J; Moro, F; Chayvialle, J-A; Cuber, J-C; Plaisancié, P
Abstract : BACKGROUND: Mucins play an important protective role in the colonic mucosa. Luminal factors modulating colonic mucus release have been not fully identified. AIM: To determine the effect of some dietary compounds on mucus discharge in rat colon. METHODS: An isolated vascularly perfused rat colon model was used. Mucus secretion was induced by a variety of luminal factors administered as a bolus of 1 ml for 30 minutes in the colonic loop. Mucin release was evaluated using a sandwich enzyme linked immunosorbent assay supported by histological analysis. RESULTS: The three dietary fibres tested in this study (pectin, gum arabic, and cellulose) did not provoke mucus secretion. Luminal administration of sodium alginate (an algal polysaccharide used as a food additive) or ulvan (a sulphated algal polymer) induced a dose dependent increase in mucin discharge over the concentration range 1–25 mg/l (p<0.05 for 25 mg/l alginate and p<0.05 for 10 and 25 mg/l ulvan). Glucuronic acid and galacturonic acid, which are major constituents of a variety of fibres, produced significant mucin secretion (p<0.05). Hydrogen sulphide and mercaptoacetate, two sulphides produced in the colonic lumen by microbial fermentation of sulphated polysaccharides, did not modify mucin secretion. Among the short chain fatty acids, acetate (5–100 mM) induced a dose dependent release of mucus (p<0.05 for 100 mM acetate). Interestingly, butyrate at a concentration of 5 mM produced colonic mucin secretion (p<0.05), but increasing its concentration to 100 mM provoked a gradual decrease in mucus discharge. Propionate (5–100 mM) did not induce mucin release. Several dietary phenolic compounds (quercetin, epicatechin, resveratrol) did not provoke mucus discharge. CONCLUSIONS: Two algal polysaccharides (alginate and ulvan), two uronic acids (glucuronic acid and galacturonic acid), and the short chain fatty acids acetate and butyrate induce mucin secretion in rat colon. Taken together, these data suggest that some food constituents and their fermentation products may regulate the secretory function of colonic goblet cells.